Smart panel design for renewable energy generation - Rudi Syahputra; Nelly Safitri; Fauzan Fauzan; Yassir Yassir; Teuku Hasannuddin; Akhyar Akhyar; Radhiah Radhiah; Zulfikar Zulfikar (Institute of Advanced Engineering and Science, 2026)
The aim of this study is to design and develop a smart panel module specifically for solar power generation, which includes three critical functions: the automatic transfer switch (ATS), the automatic main failure (AMF), and capabilities for remote monitoring and control. The ATS and AMF features employ Haiwell AT12MOT Ethernet PLC control equipment in conjunction with the Haiwell B7H Ethernet IoT cloud HMI, both designed for remote operation through an IoT system and integrated with the Haiwell cloud application. The developed PLC program interacts with HMI software that is created using NB designer. Inputs from the PLC are monitored and managed via the Haiwell cloud application, which connects with the relay designated as input for the Haiwell AT12MOT PLC. The resulting design interfaces with the PLC output located within an electrical panel specifically designed to handle industrial loads. This research results in a smart panel capable of operating in an industrial context with a power capacity of 2,200 VA. It is noteworthy that during automatic operations, load transfers between solar power systems and PLN (the national grid company of Indonesia) do not occur instantaneously; instead, there is a delay of 10 seconds as the system stabilizes back to normal conditions.